Nanoemulsions and dermatological diseases: contributions and therapeutic advances. (15th May 2018) - de Souza, Myla Lôbo; Oliveira, Douglas Dourado; Pereira, Neila de Paula; Soares, Denis Melo
Abstract: Skin disease is one of the most common human diseases and affects between 30% and 70% of individuals, which requires a lot of attention to their treatments. The delivery of active pharmacological ingredients at the topical level is a challenge because of the difficulties in overcoming the mechanical barrier created by the skin and reaching greater depths, since delivery specificities are decisive for the degree of effectiveness. In this way, the nanoemulsions emerge as a potential system for the incorporation of active substances in the cells and for the controlled release of active principles. The present article intends to review the main treatments for which the nanoemulsions were used in the field of dermatology. In addition, it discusses the results and advantages over the other dermatological therapies that are being used. The results showed that the particle size in nanoemulsions increased the contact surface area, resulting in increased drug efficacy, even in comparison with other existing pharmaceutical formulations. In conclusion, it has been shown that nanoemulsions have a better performance in efficacy, safety, permeability profile, and bioavailability compared with other formulations studied.